2018
DOI: 10.1016/j.neuropsychologia.2018.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of sensory input may improve cognitive and neural function

Abstract: Age-related hearing loss is one of the most prevalent health conditions among the elderly. Hearing loss may lead to social isolation, depression, and cognitive decline in older adults. The mechanistic basis for the association between hearing loss and decreased cognitive function remains unknown as does the potential for improving cognition through hearing rehabilitation. To that end, we asked whether the restoration of sensory input through the use of hearing aids would improve cognitive and auditory neural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 57 publications
2
59
0
4
Order By: Relevance
“…Further, cognitive gains in their hearing loss group were associated with P2 cortical auditory evoked potential (CAEP) amplitudes, suggesting that increased auditory input may provide neurocognitive benefit. Our findings are also supported by experimental evidence by Deal et al (2017) and Karawani et al (2018a), where hearing aid treatment over longer durations (>6 months) in similar ARHL populations resulted in significant improvements in cognitive function the cognitive domains of global cognitive abilities and processing speed (Deal et al, 2017) as well as improvements in working memory (Karawani et al, 2018b). In addition, long-term neurocognitive benefit has been reported in deaf adult cochlear implant recipients at 6 months and 1 year post post-treatment, where notable gains were observed in the areas of global cognitive function and executive function (Mosnier et al, 2015).…”
Section: Potential For Hearing Aid Use To Reverse Visual Cortical Crosupporting
confidence: 85%
“…Further, cognitive gains in their hearing loss group were associated with P2 cortical auditory evoked potential (CAEP) amplitudes, suggesting that increased auditory input may provide neurocognitive benefit. Our findings are also supported by experimental evidence by Deal et al (2017) and Karawani et al (2018a), where hearing aid treatment over longer durations (>6 months) in similar ARHL populations resulted in significant improvements in cognitive function the cognitive domains of global cognitive abilities and processing speed (Deal et al, 2017) as well as improvements in working memory (Karawani et al, 2018b). In addition, long-term neurocognitive benefit has been reported in deaf adult cochlear implant recipients at 6 months and 1 year post post-treatment, where notable gains were observed in the areas of global cognitive function and executive function (Mosnier et al, 2015).…”
Section: Potential For Hearing Aid Use To Reverse Visual Cortical Crosupporting
confidence: 85%
“…In another prospective study of 125 individuals aged 65 years and older, individuals with hearing aids had significant improvements in short-term memory ( Castiglione et al, 2016 ). More recently, a randomized study of 32 older adults with moderate to severe HL found that those randomized to hearing aid use demonstrated improved memory after 6 months of hearing aid use; the authors concluded that hearing aid use may improve cognition ( Karawani, Jenkins, & Anderson, 2018 ). Thus, it appears that larger prospective controlled trials are needed to understand whether or not hearing aids improve cognition among those with HL.…”
Section: Discussionmentioning
confidence: 99%
“…Audiological rehabilitation including use of hearing aids (which amplify weak sounds) are common treatments for HL. Auditory rehabilitation, training and use of hearing aids have shown to improve hearing, including the cortical and subcortical processing of speech, and associated cognitive function 66,67. Relatedly, use of hearing aids and auditory rehabilitation has been reported to mitigate depression symptoms 6870.…”
Section: Clinical Implications: Interventionmentioning
confidence: 99%